Strategies to Strengthen Mental Health Services in Hospital during Covid-19 - Niken Sasanti Ardi; Dumilah Ayuningtyas (Universitas Muhammadiyah Yogyakarta, 2021)
Psychiatric disorders that arise due to Covid-19 include anxiety, depression, psychological trauma and the use of drugs to deal with tension caused by the pandemic. A total of 535 respondents (49%) out of 2,364 respondents had thoughts about death. Hospitals must make changes and mitigate, accelerate and adapt faster. This article aims to identify best practice strategies for suicide prevention to improve mental health services in hospitals. This study used queries: